SIMEX: a swot analysis a case study on SIMEX - Foo, Sheh Ling (2014)
The objective of this final year report on SIMEX -- a Strength, Weakness, Opportunities and Threats Analysis is to give an overview of the exchange's present operating environment and future avenues of development. The purpose of doing a study on SIMEX is due to the commonly-held opinion that futures and options would be very prominent as a risk management as well as a speculative tool in the next century. The sophistication of investors are at much higher levels than before and it would be highly likely to see great interest in the trade of derivative investment products in the not-too-distant future. As such, we would like to be at the forefront of this trend and be ready for it when it comes.